Economic losses due to hemorrhagic septicaemia in India - BARDHAN, D; KUMAR, S; SEKARAN, G ANANDA; MERAJ, M; CHILAMBARASAN, M; SINGH, R K; SINGH, G; PAL, R; SINGH, Y P; VERMA, M R; KUMAR, D (The Indian Journal of Animal Sciences, 2020)
Hemorrhagic Septicemia (HS) is one of the most widely reported diseases in India. The present study aims to estimate economic losses due to it. The study uses a stratified multistage sampling technique, covering the major agro-climatic regions of the country, to ascertain the morbidity and mortality rates of HS. The sample size comprised of 10,839 dairy animals. The economic loss due to HS in bovines was worked out as sum of mortality loss, direct milk yield loss, losses due to increased abortions, drought power loss, cost of treatment and extra labour costs. Simple mathematical models were developed for the purpose of computing component-wise losses due to the disease. The economic loss per animal due to HS in India was estimated ₹ 11,904; ₹ 13,044 and ₹ 20,296 in case of indigenous and crossbred cattle and buffaloes, respectively. The share of buffaloes in total economic loss was highest (55%), followed by indigenous (28%) and crossbred (16.5%) cattle. Taking into account the uncertain ties associated the epidemiological and economic parameters, stochastic modeling was used to estimate the economic impact of HS. The expected annual economic loss due to HS in India ranges from ₹ 58.63 billion to ₹ 175.72 billion; the most likely range of expected economic losses is between ₹ 126.28–127.58 billion. Thus, from policy perspective, HS is one of the most important diseases when it comes to mitigating losses due to diseases in dairy animals.